Sokrates und die deliberative Demokratie. Zum sokratischen Politikverständnis in Platons Apologie, Kriton und Gorgias - Jedan, Christoph (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2010)
The position of Socrates in Plato’s earlier dialogues is often seen as an anticipation of contemporary political theories. This article takes issue with the claim that Socrates anticipated modern theories of deliberative democracy. It examines three early Platonic dialogues (the Apology, the Crito and the Gorgias) and argues that the Socrates presented in the dialogues is actually far more dogmatic in ethical as well as religious matters than such annexations of Socrates can acknowledge. Furthermore, Socrates does not develop a theory that would support Athenian democracy. Although politically inactive within the Athenian political framework, Socrates is nonetheless depicted in the Gorgias as formulating an “ethical” view of politics. According to this conception, true politics is always virtue oriented. It is a matter of improving the characters of one’s fellow citizens, and is detached from the question of how political power should be distributed. Socrates’ political outlook is echoed in several Hellenistic philosophical schools, the Stoics in particular.
Keywords: Plato; Socrates; Politics; Religion; Deliberative democracy